Segmentation for retain at fitness centres: contribution of service quality, expectations and satisfaction in the club - Gonçalves, Celina (2019)
How segmentation helps member retention is essential to increase the organisation's profitability. Health clubs focus on understanding their members behaviour about service quality (Fernandéz et al., 2018), expectations (Robinson, 2006) and satisfaction in the club (Gonçalves et al., 2014), detecting risk members to try to repurchase (Ferrand, Robinson, & Valette, 2010). The aim of this study is to understand the type of members that retain in the fitness organisations, regarding service quality, expectations and satisfaction in the club.